LESSONS IDENTIFIED DURING THE CONFLICTS IN UKRAINE AND GAZA IN THE DIPLOMATIC FIELD - Sinziana Iancu (Annals: Series on Military Sciences)
Resilience within the diplomatic domain ensures sustained and adaptive efforts to manage and resolve conflicts, support humanitarian needs and maintain international cooperation and stability in regions affected by conflict. Long-term diplomatic engagements build trust among conflicting parties and the international community, which is essential for sustainable peace. Resilience in diplomatic efforts is essential for navigating the complexities of the Russia-Ukraine conflict, where deeply contrasting objectives between the two nations have made negotiations challenging. Despite the difficulties, sustained diplomatic engagements are critical for maintaining international cooperation and addressing humanitarian needs. Ukraine's persistent use of international organizations, such as the United Nations and the European Union, has been influential in garnering global support and isolating Russian Federation diplomatically, even when immediate resolutions to the conflict remained elusive.